MANGROVE LITTER DECOMPOSITION SPEED IN MARINE STATION DUMAI - Nur Azizah; Joko Samiaji; Nursyirwani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study of was conducted in December 2014 - March 2015 in the area of mangrove forests Marine Station Dumai. The purpose of this study was to determine the speed of litter decomposition of mangrove and the diversity of fungi in litter of mangrove. The method used was survey method. The sampling and measurement for water quality included salinity, temperature and pH that were done directly in the field. Weighing litter carried out at the Laboratory of Marine Chemistry whereas litter decomposition data analysis and identification of fungi diversity was carried out in the Laboratory of Marine Microbiology Faculty of Fisheries and Marine Sciences University of Riau. Mangrove leaf litter decomposition was in the highest at station III with a percentage value of litter decomposition rate of 1.31% per day. The identification results in leaf litter on the mangrove areas showed that there were eight types of fungi that included two of the species Aspergillus sp., Chaetomium sp., Candida sp., Gliocladium sp., Culvularia sp., Bipolaris sp. and Exophiala sp. The most often fungi found in each observation was Gliocladium sp. The highest fungi species diversity index was at score of 2.08 on a mangrove leaf litter that was found on observation IV.Key words : mangrove , litter , decomposition rate , fungi , Dumai Marine Station